IMPLEMENTING PROJECT-BASED LEARNING TO IMPROVE FIFTH-GRADE STUDENTS’ ENGLISH LEARNING - Nurlistia; Alya Putri Ramadhani; Paulina Besty Fortinasari (Language and Educational Journal, 2024)
Project-based learning (PjBL), a teaching method, improves students' skills through projects. This study aimed to assess the impact of implementing PjBL on fifth-grade English language skills. Data collection used a qualitative approach through questionnaires and surveys. The questionnaire responses were analyzed to describe the findings, and qualitative data were gathered from a survey on students' interest in learning English. This study focused on how PjBL was implemented in fifth-grade English lessons at SDN Soronalan 2 Sawangan and students' perceptions of the method. Before using PjBL, many students (85%) had scored below 80, showing low performance. Only a few students (15%) had scores above 80. After the exposure of PjBL, many students (85%) obtained high scores above 80, and a few students (15%) got low scores. It indicated that there was a significant improvement in learning outcomes. The study concluded that PjBL effectively enhanced English learning outcomes for fifth-grade elementary students